Heavy Metal Adsorption by Magnetic Hybrid-Sorbent: An Experimental and Theoretical Approach - Simsek, Esra Bilgin; Duranoglu, Dilek; Beker, Ulker (TAYLOR & FRANCIS INC, 2012)
This study examined the sorption and desorption behaviors of Cu2+ and Pb2+ ions, which were adsorbed on the vinyl benzene chloride divinylbenzene (VBC-DVB-OH) polymer and magnetic hybrid adsorbent (VBC-DVB-OH-Fe) at pH 5. Batch and fixed bed column experiments were performed to study practical applicability and the breakthrough curves were obtained. The experimental equilibrium data, suitably fitted by the Langmuir and Freundlich isotherms, have shown that ferric oxide loaded magnetic hybrid sorbent (VBC-DVB-OH-Fe) exhibits higher adsorption capacity than vinyl benzene chloride divinylbenzene (VBC-DVB-OH) polymer. The results indicate the following order to fit the isotherms for both metal ions: Langmuir > Freundlich for polymeric sorbent and Freundlich > Langmuir for VBC-DVB-OH-Fe. The maximum adsorption capacity of VBC-DVB-OH adsorbent is 26.39 mg/g for Pb2+ and 7.93 mg/g for Cu2+ whereas it is increased to 45.81 mg/g for Pb2+ and and 25.64 mg/g for Cu2+ by using VBC-DVB-OH-Fe adsorbent. A series of column experiments were carried out to determine the breakthrough curves. The regeneration efficiency of the column runs was determined using HCl (10% v/v). The elution efficiency was 90% for each adsorbent.
Keywords: copper; heavy metal; ion exchange; lead; magnetic hybrid sorbent; magnetite; ACTIVATED CARBONS; AQUEOUS-SOLUTION; WASTE-WATER; FT-IR; REMOVAL; IONS; CR(VI); BEADS; NANOPARTICLES; EXCHANGE; Chemistry; Engineering